My Beautiful Hair - Ernest Talarico (Association of American Medical Colleges, 2014)
Abstract Introduction This is a problem-base-learning (PBL) teaching case intended for first-year medical school human gross anatomy during the course of anatomical dissection and discussion sessions, pertinent to the scalp, and the effect trauma may have on mental illness. It is an interesting case that follows a patient who, due to a traumatic accident, must be rushed to the emergency room because of an avulsed scalp. The case then discusses the patient's hospital care and resulting psychiatric issues. Thus, the focus of this case comprises anatomy of the head and scalp and to a lesser extent the anatomy and physiology of the brain with particular interest in neuronal activity. This case can also be used for second-, third- and fourth-year medical students as well as residents because of its clinical content. Some adaptation of the case material may be needed and can be done by faculty to suit the specific medical school audience without diluting the basic science and clinical usefulness of the case. Methods The PBL Group ideally consists of six students and one faculty tutor. The case is divided into three 2-hour sessions where pages are handed out, one at a time, and discussed by the group. Images are accessed for discussion where indicated within the case and prior to discussion of subsequent pages. The tutor may verbalize the guiding questions located in the Instructor's Guide to assist the PBL group in the process of the case. Sessions two and three begin with a discussion of knowledge obtained via research of learning issues from prior sessions and sharing of knowledge and resource materials. The case ends with students being supplied with case objectives/vocabulary for discussion and review. If the PBL group was successful, each participant will be able to answer the cases objectives, guiding questions, and have mastered the vocabulary. Results In the Fall 2013, this PBL case was evaluated with 27 first-year medical students, 24 second-year medical students, and 8 tutors/faculty members. All faculty/tutors and participants during each of the above evaluation periods found the case useful. Discussion The ultimate goal is not diagnosis, but is the understanding and application of basic sciences (human gross anatomy, histology, embryology and radiology, as well as pathology and some pharmacology) to an actual clinical case designed to reinforce material being learned in laboratory and discussion sessions.